Myasthenic decrement and myasthenic myopathy. A study on the effects of thymectomy. Issue 6 (June 1975) - Pinelli, P; Arrigo, A; Moglia, A
Abstract : Motor unit action potentials, M responses to repetitive nerve stimulation, and anticholinesterase tests were investigated in 12 myasthenic patients before and after thymectomy. In six of them the endarterial acetylcholine test was also carried out. Responsiveness to ACTH or to prednisone treatment was evaluated before and after thymectomy. The typical myasthenic presynaptic disorders were improved by thymectomy, while signs of myasthenic myopathy (according to Rowland's definition) were apparently increased. This process of 'functional myopathophanerosis' is discussed and explained in terms of a previous presynaptic disorder blocking the voluntary recruitment threshold of those motor units which are most affected at both presynaptic and postsynaptic level.